2021
DOI: 10.3390/ijerph19010264
|View full text |Cite
|
Sign up to set email alerts
|

Negative Ion Purifier Effects on Indoor Particulate Dosage to Small Airways

Abstract: Indoor air quality is an important health factor as we spend more than 80% of our time indoors. The primary type of indoor pollutant is particulate matter, high levels of which increase respiratory disease risk. Therefore, air purifiers are a common choice for addressing indoor air pollution. Compared with traditional filtration purifiers, negative ion air purifiers (NIAPs) have gained popularity due to their energy efficiency and lack of noise. Although some studies have shown that negative ions may offset th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…They found that the increased NAIs associated with the decreased PM improved respiratory function mainly by eight pathways including promoting energy production, anti-inflammation and anti-oxidation capacity [ 31 ]. NAIs were also observed to be an energy-efficient air purification intervention that can effectively reduce the small airway particle exposure when a sufficient NAIs concentration is obtained [ 32 ]. ALI is a syndrome of pulmonary inflammation and permeability characterized by gas exchange dysfunction associated with pathological features like pulmonary capillary endothelial cell damage, alveolar epithelial cell injury, extensive aqualung, tiny pulmonary atelectasis, microthrombi and microcirculation disturbance [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the increased NAIs associated with the decreased PM improved respiratory function mainly by eight pathways including promoting energy production, anti-inflammation and anti-oxidation capacity [ 31 ]. NAIs were also observed to be an energy-efficient air purification intervention that can effectively reduce the small airway particle exposure when a sufficient NAIs concentration is obtained [ 32 ]. ALI is a syndrome of pulmonary inflammation and permeability characterized by gas exchange dysfunction associated with pathological features like pulmonary capillary endothelial cell damage, alveolar epithelial cell injury, extensive aqualung, tiny pulmonary atelectasis, microthrombi and microcirculation disturbance [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the rooms will be ventilated in a manner similar to that used in our previous study (such as in terms of relative parameters, airflow organisation and the location of the diffusers and purifier). 46 The specific environments of rooms will be adjusted to suit the actual conditions of this RCT.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The anthropomorphic model will be placed at a fixed position beside the participant to simulate an endoscopist. The distance from the oral cavity of the participant to the oral cavity of the anthropomorphic model will be 0.8±0.1 m,45 46 and the anthropomorphic model will wear or not wear a surgical mask, according to the group allocation of the participant being examined.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…People use various non-pharmaceutical interventions (NPI) (e.g. indoor ventilation, air purifiers, ultraviolet, and masking) to reduce the infection risk of COVID-19, with increasing the fresh air exchange rate being the most popular intervention [ [6] , [7] , [8] , [9] ]. However, excessive ventilation inevitably wastes energy, particularly on hot or cold days.…”
Section: Introductionmentioning
confidence: 99%